The mediating effect of time perspectives and the moderating effect of age on the relationship between religiosity and self-efficacy - Lee, Chester Howard Manalo (Animo Repository, 2012)
This study focused on three psychological variables across adolescence, young adulthood and middle adulthood: religiosity, time perspectives (past positive time perspective and future time perspective) and self-efficacy. There were three questions asked in relation to these variables. First, do the two time perspectives (past positive time perspective and future time perspective) mediate the relationship between religiosity and self efficacy? Second, does age play a moderating role over the relationship between religiosity and self efficacy? Third, does the behavioural variable religiosity predict cognitive variables (time perspectives, self-efficacy)?- hence confirming self perception theory- that behaviours influence ways of thinking. Multiple mediator analysis, moderator analysis and path analysis were used to analyze the data coming from 314 participants belonging to three age groups: adolescence, young adulthood and middle adulthood. Results indicated that (1) the two time perspectives do play a mediating role between religiosity and self-efficacy; (2) age does play a moderating role over the relationship between religiosity and self-efficacy and (3) religiosity does predict cognitive variables such as time perspectives and self-efficacy. The implications of this study are as follows: (1) The established relationship between religiosity and self-efficacy in the literature can be explained by a mediating role of a cognitive variable (specifically time perspectives). (2) Filipino religiosity is influenced by their age which further explains why the religiosity-self efficacy relationship also changes across adolescence, young adulthood and middle adulthood. (3) The claim of self perception theory seems to be valid-at least in the context of religiosity, time perspectives and self-efficacy.